Incidence and severity of acute mountain sickness and associated symptoms in children trekking on Xue Mountain, Taiwan - Cheng, Fei-Ying; Jeng, Mei-Jy; Lin, Yin-Chou; Wang, Shih-Hao; Wu, Shih-Hao; Li, Wen-Cheng; Huang, Kuo-Feng; Chiu, Te-Fa (PLOS ONE, 2017)
Background Acute mountain sickness (AMS) occurs in non-acclimatized people after an acute ascent to an altitude of 2,500 m or higher. The aim of this study was to examine the incidence and severity of AMS and associated symptoms in children. Methods The prospective observational study included 197 healthy, non-acclimatized 11 and 12-year-old children trekking the round-trip from the trailhead to the summit of Xue Mountain, Taiwan (2,179 m to 3,886 m) over 3 days. AMS was evaluated at Qika Hut (2,460 m) on Day 1, at Sanliujiu Hut on Day 2 (3,100 m), and at the same altitude (3,100 m) after reaching the summit on Day 3. We used the Lake Louise Score (LLS) to diagnose AMS and record daily AMS-associated symptoms. We gave acetazolamide to children with mild to moderate AMS. Dexamethasone was reserved for individuals suffering from severe AMS. Acetaminophen was administrated to children with headache, and metoclopramide for those with nausea or vomiting. Results There were 197 subjects eligible for analysis. The overall incidence of AMS was 40.6%, which was higher in males and in subjects with a higher body mass index (BMI) (p < 0.05). The prevalence of AMS on Day 1 was 5.6%, which was significantly lower than that on Day 2 (29.4%) and Day 3 (23.4%). The mean LLS of all subjects was 1.77 ± 2.08. The overall incidence of severe AMS (LLS ≥ 5) was 12.5%. The mean LLS of the AMS group (3.02 ± 2.46) was significantly higher than that of the non-AMS group (0.92 ± 1.16, p < 0.001). Among the AMS group, the mean LLS was 1.00 ± 1.55 on Day 1, 4.09 ± 1.97 on Day 2, and 3.98 ± 2.42 on Day 3. The most common symptom was sleep disturbance followed by dizziness, and headache. The prevalence of headache was 46.2% on Day 2 at 3,100 m, and 31.3% on Day 3 at the same altitude after climbing the summit (3,886 m). Males experienced significantly more headache and fatigue than females (p < 0.05). The LLS and prevalence of all AMS symptoms were significantly higher in the AMS than the non-AMS group (p < 0.05). Conclusions The AMS incidence among children trekking to Xue Mountain was 40.6%. AMS is common and mostly manifests as mild symptoms. Gender (male) and a higher BMI could be considered two independent risk factors of higher AMS incidence. Sleep disturbance is the most common symptom, and the lower prevalence of headache on Day 3 may be due to the effects of medication and/or acclimatization.